IMPLEMENTASI MIND MAPPING PADA PEMBELJARAN TEMATIK KELAS VI SD NEGERI 1 GUNUNGREJO - Rosidah Nur Rohmah; Muhammad Sulistiono; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
In the learning process carried out by educators, it can also be seen from the teaching they apply to students. Many educators use methods that make them more understandable about their teaching, and also still use the old method because they are still using the old teaching. Based on the description presented, the researcher wants to conduct a research entitled "Implementation of Mind Mapping in Grade IV Thematic learning at SD Negeri 1 Gunungrejo in 2021/2022. And the researchers hope that the Mind Mapping Method can improve student learning outcomes in grade IV at SD Negeri 1 Gunungrejo. To find out the planning of the Mind Mapping Method on Thematic Learning in Class VI. To be able to find out the Implementation of the Mind Mapping Method in thematic learning in Class VI SD. To be able to know the results of the Mind Mapping Method on Thematic Learning in Class VI. In conducting this research, the researcher uses the type of case study research, which is used to obtain data by conducting field studies. That case studies are an effort to collect and organize and analyze data about certain cases with regard to the problems that arise. The attention of the researcher then the data is compared or linked to each other.